Active front-end rectifier modelling using dynamic phasors for more-electric aircraft applications - Yang, T.; Bozhko, S.V.; Asher, G.M. (IET, 2015)
The More-Electric Aircraft (MEA) has become a dominant trend for next-generation aircraft. The Electrical Power System (EPS) on-board may take many forms: AC, DC, hybrid, frequency-wild, variable voltage, together with the possibility of novel connectivity topologies. To address the stability, availability and capability issues as well as to assess the performance of the power quality and transient behaviour, extensive simulation work is required to develop the EPS architectures. The paper develops a fast-simulation model of active front-end rectifiers based on the dynamic phasor concept. The model is suitable for accelerated simulation studies of EPS under normal, unbalanced and line fault conditions. The performance and effectiveness of the developed model have been demonstrated by comparison against time-domain models in three-phase and synchronous space-vector representations. The experimental verification of the dynamic phasor model is also reported. The prime purpose of the model is for the simulation studies of MEA power architectures at system level; however it can be directly applied for simulation study of any other EPS interfacing with active front-end rectifiers.